(untitled) (Revista Contexto & Saúde, 2025)
This research approached 4- to 18-month-old children who attended daycare centers aiming to identify their neuropsychomotor development (NPMD) and home stimulation and verify the association of neonatal, socioeconomic, and environmental variables with NPMD, from the perspective of the sustainable development goals (SDGs). Cross-sectional study in 181 children, assessing their NPMD (Alberta Infant Motor Scale – AIMS and Denver II screening test) and contexts (Affordances in the Home Environment for Motor Development Infant Scale – AHEMD-IS). The data were analyzed with chi-square independence tests. The NPMD of 45.3% of the children were at risk/delayed; 31.5% had little home stimulation. There was an association with NPMD perceived as typical by parents (p=0.005), who were 7.5 times more likely to correctly identify NPMD. There was an association with maternal educational attainment (p=0.011); mothers with lower educational attainment were up to 3.8 times more likely to have at-risk babies. Better AHMED-IS Physical Space (p=0.006), Variety of Stimulation, and Total scores (p<0.001) were protective to NPMD. The results showed that SGD 3 and 4 are threatened by the lack of home stimulation and low maternal educational attainment; hence, the parental perception must be given importance. These findings may optimize NPMD protective measures proposed by SDGs, providing services and actions to improve early childhood development.